Smart Parenting Demokratis Dalam Membangun Karakter Anak - Rozana, Asiatik Afrik; Wahid, Abdul Hamid; Muali, Chusnul (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2018)
This paper presents the Smart Parenting Democratic in Building the Character of the Child. The character that is embedded in a child is strongly influenced by the role of the parent, in which the parent becomes the first person in terms of planting moral, religious, social and other values. Related parenting methods of parenting, there are various types that can be used such as authoritarian parenting, permissive parenting, and democratic parenting. Therefore, to be a smart parent is very necessary to always develop a method of care that is considered good to be applied to his children. Democratic parenting is one of the most effective parenting styles compared to other parenting styles.